Corporate governance and capital structure decisions: moderating role of inside ownership - Chowdhury, Suman Paul; Ahmed, Riyashad; Debnath, Nitai Chandra; Ali, Nafisa; Bhowmik, Roni (Multidisciplinary Digital Publishing Institute, 2024)
This study empirically investigates the association between board attributes and capital structure decisions of non-financial listed firms in Bangladesh. This study also investigates how this association is shaped and moderated by the level of insider ownership. The current study takes 3096 firm-year observations of firms that are listed on the Dhaka Stock Exchange from 2004 to 2023. Multiple regression analysis on panel data was used, and pooled OLS was selected by resolving stationary issues. Moreover, this study used lagged variables and a GMM estimator to address endogeneity. The results show that both board size and board independence are more positively correlated with a firm’s leverage under conditions of a high level of inside ownership. On the other hand, without the moderating effect of inside ownership, gender diversity on the board does not have any significant impact on a firm’s leverage, and it turns into a positive association due to the moderating effect of inside ownership. This result is consistent with the existing theory and previous findings. After the introduction of corporate governance guidelines, the inside owners’ effect on board size and board independence became substantial, indicating that corporate governance guidelines with the moderating role of inside ownership play a significant role in capital structure decisions in Bangladeshi listed firms.